REKONSTRUKSI HUKUM ATAS RUU TINDAK PIDANA PENYELENGGARAAN PERADILAN: UPAYA PENINGKATAN KINERJA KOMISI YUDISIAL DAN MAHKAMAH AGUNG - Junior B. Gregorius (LPPM Universitas Ekasakti, 2024)
This article was written with the aim of analyzing how the legal reconstruction of the Judicial Administration-Contempt of Court Crime Bill (